Penanaman Mangrove Guna Mengurangi Resiko Banjir Di Sine Kecamatan Kalidawir Tulungagung - Anandra Al Ahmad Rizqi; Arina Widia Ningtias; Rizqa Nadhifah; Dian Eliza Aquarista; Hany Nurpratiwi (Journal of Creative Student Research, 2023)
The characteristics of coastal plants in the form of river estuaries, estuaries, and deltas in protected areas in the sub-tropics and tropics are the notions of mangrove plants. It can be concluded that mangrove plants are ecosystems that exist between sea and land with conditions in the form of productive and extensive forests. Mangrove plants are also often called coastal forests, mangrove forests, brackish forests, tidal forests because mangrove plants live near the coast and have an important role in their ecological value to support coastal development activities and marine conservation. This research aims to find out the benefits and functions of mangroves, the types of mangroves, the meaning of mangroves, their role in overcoming some of the existing problems, as well as the differences before and after the planting of mangroves on the coast of Sine Tulungagung. This research method uses qualitative data which is a method for collecting and conducting observations, interviews, documentation, and analysis of various documents such as written documents, namely various journal reference sources and others in a descriptive way.